Pembangunan Ekonomi Daerah Melalui Pengelolaan Keuangan Daerah dalam Rangka Mewujudkan Good Governance - Lies Ariany (Fakultas Hukum, Universitas Islam Bandung, 2010)
One element of the Indonesian reform programs is to provide a greater autonomous to regional government. The Law No.32 of 2004 on Regional Government has changed centralized government system towards decentralization one by providing a real and accountable regional autonomous For this purpose, under this Law an autonomous region must have the authority and ability to manage the financial sources to adequately fund the execution of its region government. According to this Law, the implementation of the regional autonomy is designed to improve the people prosperity by taking into account the public interest and aspiration. This article examines the problems arise in regional financial management in the framework of realizing good governance. Apparently, the financial problem arises in the context of the regional government practice. The article concludes that the establishment of public sector oriented regional financial management system is to create a good governance based on three pillars: transparency, accountability and participative.